GSI kids play parachute : [20 feet] [library of things]. (Garg Sports International, 2020)
"The play parachute, also known as Kids Parachute; Rainbow Parachute or Kids Play Parachute, are used as a recreational activity in schools, birthday parties, Kindergartens, Picnics, playgrounds, daycare centers, and gym programs. These Fun Parachutes are designed for use in both indoor and outdoor environments and suitable for group fun for both young and adults. Playground parachutes are used by arranging children at the outside, who then vigorously wave the handles up and down using the handles provided. Through the practice, you can develop social, perceptual and motor skills, along with physical education exercise and conditioning of muscles."--Manufacturer's description.